Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
Ta có A=\(\left(ab+bc+ca\right)\left(\frac{1}{a}+\frac{1}{b}+\frac{1}{c}\right)-abc\left(\frac{1}{a^2}+\frac{1}{b^2}+\frac{1}{c^2}\right)\)
=\(2\left(a+b+c\right)+\frac{ab}{c}+\frac{bc}{a}+\frac{ca}{b}-\frac{ab}{c}-\frac{bc}{a}-\frac{ca}{b}=2\left(a+b+c\right)\)
\(A=\left(a+b\right)\left(a^2-ab+b^2\right)+3ab\left[\left(a+b\right)^2-2ab\right]+6a^2b^2=a^2-ab+b^2+3ab\left(1-2ab\right)+6a^2b^2\)
=\(\left(a+b\right)^2-3ab+3ab-6a^2b^2+6a^2b^2=1\)
2) Ta có \(A=\left(a-1\right)\left(b-1\right)\left(c-1\right)=abc-ab-bc-ca+a+b+c-1=0\)
Tết rồi còn hok
\(a^2+b^2+c^2=1\Rightarrow a^2;b^2;c^2\le1\Rightarrow-1\le a;b;c\le1\)\(\Rightarrow\hept{\begin{cases}1-a\ge0\\1-b\ge0\\1-c\ge0\end{cases}}\)
Từ \(a^2+b^2+c^2=a^3+b^3+c^3=1\Rightarrow a^2+b^2+c^2-a^3-b^3-c^3=0\)
\(\Leftrightarrow a^2\left(1-a\right)+b^2\left(1-b\right)+c^2\left(1-c\right)=0\)
Mà \(1-a;1-b;1-b\ge0\) (cmt)
nên \(a^2\left(1-a\right)+b^2\left(1-b\right)+c^2\left(1-c\right)\ge0\)
Dấu "=" xảy ra \(\Leftrightarrow a=b=c=1\)
\(\Rightarrow a^2+b^{2012}+c^{2013}=3\)